Design of Luxury Train Seat Integrating Emotional Perception and Local Wisdom Approaches - Afif Hakim; Bambang Suhardi; Pringgo Widyo Laksono; Mirwan Ushada; Jafri Mohd Rohani (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2025)
Although the physical ergonomics of seat design have been extensively studied, emotional comfort is still largely overlooked, especially in public transport. This study addresses this gap by incorporating passengers' emotional perceptions into the design of luxury train seats, in response to documented user discomfort which transcends physical dimensions. The aim was to design seats based on the emotional needs of users and the principles of Kansei engineering, incorporating elements of Javanese cultural values as a form of local wisdom. Emotional responses were captured using Kansei words derived from user interviews, online reviews, and from the expertise of local practitioners. The designs included batik and Javanese decorations. A statistical analysis using Quantitative Theory of Type I (QTT1) identified design elements corresponding to semantic differences between Kansei words. Analysis revealed that the dominant emotional dimension is creative, as indicated by the highest multiple of R-squared 0.9785. This dimension has been operationalized in 14 concrete design elements of the proposed seating concept. The innovative use of batik motifs on the seat backrests was a distinctive feature and underlined the fact that users perceived cultural integration as central to the creative dimension. The study concluded that the integration of emotional perception, represented by the creative dimension, and local wisdom, represented by the batik elements, is a viable strategy for the design of culturally distinct and emotionally attractive luxury train seats. It shows that the culturally rooted approach of Kansei Engineering contributes to the welfare of users.